DIGITALTOURISM: OPPORTUNITIES AND CHALLENGES FOR TOURISM IN INDONESIA - Benny Ade Saputra; Nina Mistriani (JURNAL ILMIAH EDUNOMIKA, 2024)
Abstract The concept of tourism has taken a step higher following digital flows in every sector and one of them is the tourism secto. One side of the digital tourism concept can make tourism in Indonesia more advanced through digital marketing, the concept of virtual tourism, and so on. However, on the other hand, the concept of digital tourism can actually become a new type of digital crime in Indonesia in the form of fraud, cyber crimes, data breaches, and so on. This research is qualitative research with a descriptive approach which contains a description of the advantages and disadvantages of the presence of the Digital Tourism concept in Indonesia. The data that researchers use in this article is primary data that researchers obtained from credible websites, scientific articles, books, and so on which are usually used in scientific articles. Advantages and disadvantages in this research are measured using the standard SWOT analysis technique. The result n this article show The concept of digital tourism can make tourism even busier, known to many people because marketing methods through digital systems have a wide reach, save time and have minimal costs which in the end can increase income from the world of Indonesian tourism. On the other hand, the concept of digital terrorism can create new types of crime including online fraud, theft of personal data, and other types of cyber crime. From the SWOT analysis carried out by researchers, the Digital Tourism concept has many advantages and disadvantages. To minimize losses as much as possible, protection is needed. Keywords: Digitaltourism, Opportunities, Challenges